Efeitos do exercício físico materno sobre alterações em marcadores do processo inflamatório e do eixo hipotálamo-hipófise-adrenal em camundongos estressados no periodo pré-natal - Costa, Mariana Severo da (2022)
Introduction: Chronic stress causes physiological changes. When it occurs in the gestational period, which is a time sensitive to several internal and external factors, with high plasticity and which can affect fetal development, it can increase the risks of respiratory, neuroendocrine and inflammatory diseases that are associated with increased activation of the hypothalamic-pituitaryadrenal (HPA) axis. The HPA axis is important for metabolic and neural functions, for lung maturation and for the modulation of pro-inflammatory cytokine secretion. On the other hand, the search for prevention methods for the effects generated by stress is relevant, with physical exercise being one of the possible strategies, since it has therapeutic and protective effects, helping to reduce symptoms generated by stress and preventing various diseases. Objective: To evaluate the effects of physical exercise before and during the gestational period on changes in markers of the inflammatory process and the HPA axis in the brain and lungs of prenatally stressed newborn mice. Methods: Balb/cByJ females and males were used. The pregnant females were divided into three groups: control (CONT); prenatal stress by restraint (PNS); and physical exercise before and during the gestational period and prenatal stress by restraint (PNS+EX). After the division, a 3-week exercise protocol was initiated. On the eighth day of gestation, the females returned to the exercise protocol and the stress protocol was started until the 21st day of gestation (G21/PND0). The females underwent cesarean section and the pups were removed for brain and lung removal (PND0). In another cohort of animals, the same analyzes were performed on the 10th day of life (PND10). After tissue collection, the markers of GR, MR, IL-6, IL-10 and TNF were analyzed through gene expression in the brain and in the lungs, and MMP-2 was evaluated through protein expression only in the lungs. Results: The animals in the PND0 group demonstrated effect of exercise with reduction in IL-6 and an increase in IL-10 in the brain. In the lung, the exercise did not reverse the effects of stress that reduced the expression of all evaluated markers. The exercise in PND10 animals reversed the effects generated by stress with the reduction of MR, IL-6 and IL-10 in the hippocampus. A positive effect of exercise on the lung was observed with the reduction of GR. Male animals in the hippocampus showed a reduction in GR showing only an effect of stress. In the lung, an effect of stress was also observed on GR with its decrease and effect of exercise with the reduction of MR. In the protein expression of MMP-2, there was no significant difference in both groups, sex or day of life. Conclusion: Prenatal stress altered the inflammatory response and regulatory markers of the HPA axis, both in the lung and in the brain on both days analyzed. Physical exercise was able to reverse the effects of stress on some of the studied markers.